Mechanism of activity and toxicity of Nystatin-Intralipid. (May 2013) - Semis, Rita; Kagan, Sarah; Berdicevsky, Israela; Polacheck, Itzhack; Segal, Esther
<x xml:space="preserve">Abstract</x> A novel lipid formulation of Nystatin (NYT), Nystatin-Intralipid (NYT-IL), which was found to be more active and less toxic in vitro and in vivo, was developed in our laboratory. The aim of the present study was to explore the possible mechanisms underlying its biological activity. To assess mechanisms affecting fungal cells we conducted the following experiments: killing kinetics, scanning and transmission electron microscopy (EM), measurements of potassium ion leakage and susceptibility in the presence of ergosterol. To study mechanisms affecting mammalian cells, we evaluated the effect of NYT-IL on a kidney cell line, with respect to viability, metabolic activity, potassium leakage and internalization of FITC-labeled human transferrin. NYT-IL exhibited killing kinetics patterns against Candida albicans similar to those of NYT and caused disruption of fungal cells and potassium ion leakage. Susceptibility tests showed that NYT-IL had lower antifungal activity in the presence of ergosterol. Thus, NYT-IL acts apparently by damaging fungal membrane, possibly through interaction with ergosterol, and maybe by additional modes of action. NYT-IL did not cause potassium leakage from mammalian kidney cells at any tested concentration and was not cytotoxic, whereas NYT, at high concentrations, led to K+ leakage and was cytotoxic. Furthermore, the high NYT concentration interfered in the internalization process of human transferrin receptor (hTfnR) while NYT-IL did not. In summary, the Intralipid formulation of NYT diminishes the mechanisms responsible for toxicity to mammalian cells but preserves mechanisms of action against fungi, thereby suggesting superiority of NYT-IL as compared to NYT as an antifungal agent.